Field-free orientation of LiH molecule induced by two-color femtosecond and terahertz laser pulses. (9th April 2019) - Wang, Shuo; Li, Huifang; Zhan, Weishen; Tao, Hongcai
Abstract: We theoretically study the field-free molecular orientation by the combination of a two-color femtosecond laser pulse and a time-delayed terahertz (THz) laser pulse, with LiH as the prototype molecule. It is shown that the molecular hyperpolarizability is a vital parameter in achieving molecular orientation according to the pre-excitation created by an intense two-color femtosecond laser pulse. The relative amplitude of the two-color femtosecond pulse is discussed. In addition, the center frequency of the THz laser pulse is chosen on the basis of the pre-excited population distributions. The carrier-envelope phase of the THz laser pulse as well as the delay time between the femtosecond laser pulse and THz laser pulse are adjusted to achieve a high orientation degree. In addition, the effect of temperature on molecular orientation is also discussed. Finally, according to the population distributions at room temperature, the parameters of the THz laser pulse are re-optimized, and the achieved maximal orientation degree is 0.221 at 300 K.